With all her heart [large type] - Irvin, Kelly (Irvin, Kelly. Amish calling, 2025)
"Bonnie is successful in her crafts shop but fears no man will see past her disability to her strong and loving heart. Elijah dreams of leaving the family business to focus on his carvings. Can they find a new path together?"--